Facts versus words: the influence of issues in the process of shaping the public agenda - Bazaga Fernández, Isabel; Tamayo Sáez, Manuel; Carrillo, Ernesto (Cuadernos de Gobierno y Administración Pública, 2022)
This paper tries to show how the characteristics of a topic can affect the cycle of attention that citizens pay to it. Starting from different theories on the formation of the public agenda and resorting to multiple triangulation, it analyzes the evolution of the priorities given by the Spanish to the issues of housing, banking and evictions. The independent variables examined are: the cultural context and the economic and political situation; the real conditions of the problems and public policies; the behaviors of the actors; and the interests and values ​​of individuals. The results obtained show how the influence of these factors was different in each topic: while in some the determining factors are the policies and the evolution of the real conditions of the problem, in others it is the presidential rhetoric, the attention of the media and the narrative of social movements. The context and the interests and values ​​of individuals also influence, introducing specific biases in each topic, but with a moderate intensity. Whether facts (policies and the evolution of the problem) or words (presidential rhetoric, the narrative of advocacy coalitions and media attention) influence the public agenda more, depends on the issue and, in particular, on whether citizens know it or not through their own experience and that of the groups with which they relate.